2021
DOI: 10.1007/s00109-021-02094-y
|View full text |Cite
|
Sign up to set email alerts
|

Targeted 1H NMR metabolomics and immunological phenotyping of human fresh blood and serum samples discriminate between healthy individuals and inflammatory bowel disease patients treated with anti-TNF

Abstract: Inflammatory bowel disease is a multifactorial etiology, associated with environmental factors that can trigger both debut and relapses. A high level of tumor necrosis factor-α in the gut is the main consequence of immune system imbalance. The aim of treatment is to restore gut homeostasis. In this study, fresh blood and serum samples were used to identify biomarkers and to discriminate between Crohn’s disease and ulcerative colitis patients under remission treated with anti-TNF. Metabolomics based on Nuclear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 40 publications
(62 reference statements)
2
12
0
Order By: Relevance
“…In another study, Scoville et al reported a decrease in essential (leucine, lysine, and valine), semi-essential (arginine and glutamine), and nonessential (serine) amino acids in CD serum samples compared to control subjects, but no differences in serum amino acids in UC compared with controls [25]. Consistently with previous studies, Notararigo et al found lower levels of creatine, proline, and tryptophan in UC patients, reflecting a deficit in the absorption of essential amino acids in the gut [27].…”
Section: Metabolic Alterations Due To Compromised Intestinal Barriersupporting
confidence: 78%
See 4 more Smart Citations
“…In another study, Scoville et al reported a decrease in essential (leucine, lysine, and valine), semi-essential (arginine and glutamine), and nonessential (serine) amino acids in CD serum samples compared to control subjects, but no differences in serum amino acids in UC compared with controls [25]. Consistently with previous studies, Notararigo et al found lower levels of creatine, proline, and tryptophan in UC patients, reflecting a deficit in the absorption of essential amino acids in the gut [27].…”
Section: Metabolic Alterations Due To Compromised Intestinal Barriersupporting
confidence: 78%
“…Recently, Notararigo et al used NMR to detect unique biomarkers for different IBD classes, reporting higher levels of homoserine-methionine and isobutyrate in ileocolonic CD. In addition, among the three CD location types, according to the Montreal classification (ileocolic, ileal, and colonic), only ileocolonic showed significant differences versus control subjects [27].…”
Section: Metabolomics Use To Distinguish CD From Uc and The Different Ibd Subclassificationsmentioning
confidence: 87%
See 3 more Smart Citations